La visión heroica sobre la independencia de Antioquia (2010)
ABSTRACT: It is evident the predominance of the heroic visions on the independence of Antioquia. The historians ascribed to the Academia Antioqueña de Historia, the heirs of a historiography tradition that emphasizes on illustrious personages, and conclusive moments of the regional independence, have been compromised in this labor of turning someone into a hero. Heroes are not always military men; some priests, a limited number of women, and few public men are joined to this select group. According to this historiography, both contributed to make feasible the campaign of emancipation: the priests harangue the population, they model the project of a Christian Republic, and they also gave economic contributions; the women educated the heroes with love and abnegation, and they waited their return from the war in a Marian resignation; the politicians helped to the new republican constitutional order with their knowledge and patriotic power.